A Phase Ia study to assess the safety and immunogenicity of new malaria vaccine candidates ChAd63 CS administered alone and with MVA CS - De Barra, E; Hodgson, S; Ewer, K; Bliss, C; Hennigan, K; Collins, A; Berrie, E; Lawrie, A; Gilbert, S; Nicosia, A; McConkey, S; Hill, A (Public Library of Science, 2014)
Background Plasmodium falciparum (P. falciparum) malaria remains a significant cause of mortality and morbidity throughout the world. Development of an effective vaccine would be a key intervention to reduce the considerable social and economic impact of malaria. Methodology We conducted a Phase Ia, non-randomized, clinical trial in 24 healthy, malaria-naïve adults of the chimpanzee adenovirus 63 (ChAd63) and modified vaccinia virus Ankara (MVA) replication-deficient viral vectored vaccines encoding the circumsporozoite protein (CS) of P. falciparum. Results ChAd63-MVA CS administered in a heterologous prime-boost regime was shown to be safe and immunogenic, inducing high-level T cell responses to CS. With a priming ChAd63 CS dose of 5×109 vp responses peaked at a mean of 1947 SFC/million PBMC (median 1524) measured by ELIspot 7 days after the MVA boost and showed a mixed CD4+/CD8+ phenotype. With a higher priming dose of ChAd63 CS dose 5×1010 vp T cell responses did not increase (mean 1659 SFC/million PBMC, median 1049). Serum IgG responses to CS were modest and peaked at day 14 post ChAd63 CS (median antibody concentration for all groups at day 14 of 1.3 µg/ml (range 0–11.9), but persisted throughout late follow-up (day 140 median antibody concentration groups 1B and 2B 0.9 µg/ml (range 0–4.7). Conclusions ChAd63-MVA is a safe and highly immunogenic delivery platform for the CS antigen in humans which warrants efficacy testing.